INVESTIGATING THE IMPACT OF HONESTY IN ICT ON CYBER CRIME - N.Vivekananda, Dr.R.Meenakshi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The study explores the intricate relationship between honesty in Information and Communication Technology (ICT) usage and its impact on cyber crime. It undertakes a comprehensive investigation by surveying 300 participants from diverse global backgrounds, aiming to elucidate how ethical conduct in ICT can mitigate or exacerbate cyber criminal activities.Methodologically, the research employs an online survey questionnaire to gather data, subsequently employing both descriptive and inferential statistical analyses. These analyses include correlation and regression techniques to discern patterns and predictive relationships among variables.